2020
DOI: 10.1111/ejss.13021
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemical leaching reduction in biochar‐amended tropical soils of Belize

Abstract: The aim of this study was to determine the effects of biochar addition on agrochemical leaching in tropical soils of Belize. Biochars were produced from mixed softwood, rice husk and miscanthus straw, each pyrolysed at 700 C. Loam, sandy silt loam and clay loam tropical soils were amended with 0, 1, 2.5 and 5% (w/w) biochar to determine atrazine, diuron, enrofloxacine, oxytetracycline and tetracycline absorption in batch studies following OECD 106 guidelines. FOCUS groundwater modelling was performed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Rice residues-based biochars have already been reported to increase sorption capacity for pesticides [26,[92][93][94]. Ren et al [95] also found better sorption capacity of rice biochar for carbaryl with increasing pyrolysis temperature, with increased sorption obtained at 700˚C.…”
Section: Plos Onementioning
confidence: 96%
“…Rice residues-based biochars have already been reported to increase sorption capacity for pesticides [26,[92][93][94]. Ren et al [95] also found better sorption capacity of rice biochar for carbaryl with increasing pyrolysis temperature, with increased sorption obtained at 700˚C.…”
Section: Plos Onementioning
confidence: 96%
“…Another study of an agrochemical was presented in the session dedicated to Soil amendments; the contribution of Aldana, Hazlerigg, Lopez-Capel, and Werner (2021) presents results of batch studies in which the sorption and retention of atrazine, diuron, enrofloxacin, oxytetracycline and biochar applied in different doses to tropical soils with different texture was investigated. They identified rice husk biochar as an amendment that can efficiently reduce the leaching of the selected agrochemicals.…”
mentioning
confidence: 99%